Globalization and Collective Labor Rights1. Issue 1 (20th January 2016) - Blanton, Robert; Blanton, Shannon Lindsey
Abstract : The impact of globalization has been a perennial source of contention, and issues regarding labor rights have been a visible aspect of this struggle. Despite the popular controversy about a potential "race to the bottom" regarding globalization and labor rights, the empirical record on these linkages remains mixed. Moreover, despite the multifaceted nature of globalization, extant literature in this area has focused purely on several specific facets of economic globalization, such as trade and FDI. We focus on two additional aspects of globalization, social and political integration, as well as a broadly based measure of economic globalization, and examine how they influence collective labor rights—both in terms of labor laws, as well as their enforcement in practice—in the developing world from 1986 to 2002. We find that all three facets of globalization are negatively related to labor rights. Specifically, social, political, and economic globalization are related to the decoupling of labor practices from extant labor laws; that is, labor practices deteriorate while labor laws remain largely unaffected.